Cumulative lifetime stress exposure, depression, anxiety, and well-being in elite athletes: A mixed-method study. (January 2021) - McLoughlin, Ella; Fletcher, David; Slavich, George M.; Arnold, Rachel; Moore, Lee J.
Abstract: Research suggests that elite athletes are at increased risk of poor mental health, partly due to the intense demands associated with top-level sport. Despite growing interest in the topic, the factors that influence the mental health and well-being of elite athletes remain unclear. From a theoretical perspective, the accumulation of stress and adversity experienced over the life course may be an important factor. To investigate this possibility, we employed a mixed-method design to: (a) examine whether cumulative lifetime stress predicted depression, anxiety, and well-being in elite athletes; and (b) help explain why cumulative lifetime stress exposure might have resulted in poor mental health and well-being. Ninety-five elite athletes ( M age = 29.81, SD = 10.88) completed the Stress and Adversity Inventory, Patient Health Questionnaire, Generalized Anxiety Disorder 7-item scale, and the Scales of General Well-Being. Hierarchical regression analyses revealed that total count and severity of lifetime stressor exposure significantly predicted greater depression ( β = .42, p < .001; β = .46, p < .001) and anxiety symptoms ( β = .34, p = .003; β = .28, p = .018), and worse well-being ( β = -.42, p < .001; β = -.30, p = .015). Semi-structured interviews were then conducted with six athletes. Thematic analysis revealed that cumulative lifetime stress exposure fostered poor mental health and well-being by promoting maladaptive long-term coping strategies, increasing susceptibility to future stress, and limiting interpersonal relationships. We believe these findings can help practitioners identify, and intervene accordingly with, elite athletes at risk of experiencing stress-related mental health problems. Highlights: Greater lifetime stress predicted poorer mental health and well-being. Greater lifetime stress promoted the use of maladaptive coping strategies. Greater lifetime stress limited the development of interpersonal relationships. Greater lifetime stress made athletes more susceptible to future stressors.